Les aménagements portuaires antiques de la Vesle à Reims/Durocortorum (Marne) - David Gucker (Gallia)
In Reims the urban development of the area “ZAC du Vieux Port”, along Boulevard Henrot, was preceded by a major preventive archaeological excavation covering an area of 4,000 m2. This operation provided the opportunity to uncover almost 50 m of the antique right bank of the Vesle river. This watercourse, on which is based the enclosure dated to the Early Roman Imperial period, in fact demarcates the western limit of the oppidum of Durocortorum, capital of the province of Gaul in Belgium. Around 15-20 AD (phase 1), the river bank was reinforced stabilised by a wood and chalk construction with a ramp and an embankment. The purpose of these constructions was to protect the bank against floods and also to facilitate the port, economic and craft activities of this urban sector. The abandonment of the embankment towards the mid-1st c. AD marks an important transition. Until 65-70 AD a causeway lined with wooden gutters was laid out. Between the last third of the 1st c. AD and the beginning/middle of the 2nd c. AD a pavement lined with wooden gutters was built (phase 2). An important stage in the development of this part of the city was reached, when it took on a more “urban” character. Large-scale works were undertaken to create new areas to accommodate a major urban expansion. These involved both the construction of a new quay in front of the previous one, and the spreading of large chalk embankments to stabilise the clayey sediments linked to the river to the north and south-east. The layout of the new quay, which is practically linear, definitively established the boundary between the river and the built surfaces. This is a transitional stage that prefigures a new organisation of this sector to incorporate it into the urban space. As a result of this work the street was equipped with a new roadway. A building was erected in front of the street and near the river, whereas the first masonry buildings were created in the southern part of the excavated area. The following period, from the mid-2nd c. AD until the beginning of the 4th c. AD, was a period of masonry constructions (phase 3) and confirms the further development of this sector and its definite incorporation into the antique settlement. The previously built quay was replaced by a new, much huger construction, which takes its layout and also its orientation from the urban fabric of the ancient city. Similarly, the street was redeveloped and given a new surface, gutters and pavements. At the outlet of the roadway onto the river two lines of piles with large cross-sections seem to correspond either to the remains of a structure allowing the crossing (bridge or footbridge) or to a facility for loading or unloading products or foodstuffs transported on the river. Set back from the river and the street, large areas were filled in and new constructions were established and used for craft activities. The general aspect of the district therefore remains unchanged and no major changes are observed during this phase. Finally, an imposing building hosting a series of ovens was constructed in 306-307 AD (phase 4). Its walls, almost 1 m wide, are supported by hundreds of oak piles. There are no clues as to the purpose of this complex, and its relationship with the river, if it exists, is outside the excavated area. The building was destroyed at the turning point of the 4th and 5th c. AD.